Beat the heat: how to become a gold medalist at the Tokyo Olympics - Eijsvogels, T. M.; de Korte, J. Q.; Bongers, C. C. (Temperature, 2021)
"Faster, higher, stronger" is the official Olympic motto and illustrates that participating athletes are expected to deliver extraordinary performances to entertain spectators and achieve the highest possible ranking. For this purpose, every athlete spent multiple years of hard training and intense preparations to succeed in their Olympic dream: become a gold medalist. The stakes are high. From fame and financial prosperity to the happiness of fulfilling a successful career. But the competition is tough and the difference between winning and losing is small, and seems to become smaller in every Olympic cycle. Therefore, Olympic performances are no longer a one (wo)man show, but a team effort instead.